Externalizing problems among Kosovar adolescents: pubertal correlates in girls and boys - Elona Krasniqi; Alexander T. Vazsonyi; Panajotis Cakirpaloglu (International Journal of Adolescence and Youth)
Pubertal timing and pubertal developmental status or stage have been associated with the rates of externalizing problems among youth, particularly in vulnerable developmental contexts including cultures undergoing rapid transformations. The present study tested the extent to which pubertal timing and pubertal developmental status were associated with delinquent and aggressive behaviours, in girls and boys. It also tested whether sex moderated these relationships. Data were collected from N = 1,342 Kosovar adolescents (665 girls; M age = 13.26 years, SD = 1.27; 677 boys M age = 13.19 years, SD = 1.31). No associations were found for the relationship between pubertal timing and externalizing problems in boys and girls. The findings provided support for a positive association between pubertal developmental status/stage and both delinquent and aggressive behaviours, in both girls and boys. The study highlights that pubertal timing and pubertal status/stage have important yet independent effects on externalizing problems.